Hormonal Modulation of Breast Cancer Gene Expression: Implications for Intrinsic Subtyping in Premenopausal Women - Bernhardt, Sarah M.; Dasari, Pallave; Walsh, David; Townsend, Amanda R.; Price, Timothy J.; Ingman, Wendy V. (Frontiers in Oncology, 2016)
Clinics are increasingly adopting gene expression profiling to diagnose breast cancer subtype, providing an intrinsic, molecular portrait of the tumour. For example, the PAM50-based Prosigna test quantifies expression of 50 key genes to classify breast cancer subtype, and this method of classification has been demonstrated to be superior over traditional immunohistochemical methods that detect proteins, to predict risk of disease recurrence. However, these tests were largely developed and validated using breast cancer samples from post-menopausal women. Thus, the accuracy of such tests has not been explored in the context of the hormonal fluctuations in estrogen and progesterone that occur during the menstrual cycle in pre-menopausal women. Concordance between traditional methods of subtyping and the new tests in pre-menopausal women is likely to depend on the stage of the menstrual cycle at which the tissue sample is taken, and the relative effect of hormones on expression of genes versus proteins. The lack of knowledge around the effect of fluctuating estrogen and progesterone on gene expression in breast cancer patients raises serious concerns for intrinsic subtyping in pre-menopausal women, which comprise about 25% of breast cancer diagnoses. Further research on the impact of the menstrual cycle on intrinsic breast cancer profiling is required if pre-menopausal women are to benefit from the new technology of intrinsic subtyping.